Secrets from the past - Bradford, Barbara Taylor, 1933- (New York : St. Martin's Press, 2013)
Leaving her successful job after the unexpected death of her famous father, photojournalist Serena Stone risks her life to save a former lover and discovers an archive of her late father's work in war-torn Libya that reveals a shocking truth about her parents' marriage.
Keywords: Arab Spring, 2010- -- Fiction; Women photographers -- Fiction; Photojournalists -- Fiction; Life change events -- Fiction; Family secrets -- Fiction; Rescues -- Fiction; Fathers -- Fiction; War photographers -- Fiction; Libya -- Fiction